A survey of Arab-Israeli relations, 1947-2001 - Lea, David, 1972-; Rowe, Annamarie (Europa, 2002)
Impartial documentation and background information fundamental to the understanding of Arab-Israeli relations. Key Features: * Covers in detail the years since the first Arab-Israeli war and the statehood of Israel, in 1947-48, to the most recent developments in relations between Israel, the emerging Palestinian political entities and the Arab States * A chronology provides an at-a-glance record of events from 1947-2001 * A Documents on Palestine section gives essential background to the various ongoing areas of dispute * Profiles.